Prevalence and risk factors of active pulmonary tuberculosis among elderly people in China: a population based cross-sectional study - Can-You Zhang; Fei Zhao; Yin-Yin Xia; Yan-Ling Yu; Xin Shen; Wei Lu; Xiao-Meng Wang; Jin Xing; Jian-Jun Ye; Jian-Wei Li; Fei-Ying Liu; Jian-Lin Wu; et al. (BMC, 2019)
Abstract Background The problem of population aging is a critical public health concern in modern China, and more tuberculosis (TB) control efforts are needed to reach elderly people at high priority. In this study, we aim to determine the prevalence and identify the risk factors of TB among elderly people in China. Methods A multistage cluster-sampled cross-sectional survey was conducted in 2013, and 27 clusters were selected from 10 counties of 10 provinces in China. All consenting participants greater than or equal to 65 years of age were screened for pulmonary TB with a chest X-ray (CXR) and a symptom questionnaire. Three sputum specimens for bacteriological examination by microscopy and culture were collected from those whose screening was positive. Prevalence was calculated, a multiple logistic regression model was performed to confirm the risk factors, and population attributable fraction (PAF) of each risk factor was calculated to indicate the public health significance. Results Of 38 888 eligible people from 27 clusters, 34 269 participants finished both questionnaire and physical examination. There were 193 active pulmonary TB cases, 62 of which were bacteriologically confirmed. The estimated prevalence of active pulmonary TB and bacteriologically confirmed TB in those 65 years of age and older was 563.19 per 100 000 (95% CI: 483.73-642.65) and 180.92 per 100 000 (95% CI: 135.89-225.96), respectively. Male sex, older age, living in rural areas, underweight, diabetes, close contact of pulmonary TB (PTB) and previous TB history are all risk factors for TB. The risk of TB increased with increasing age and decreasing body mass index (BMI) after adjusting for other factors, and there is a positive dose-response relationship. Conclusions In China, active case finding (ACF) could be implemented among elderly people aged 65 and above with underweight, diabetes, close contact history and previous TB history as a priority, which will get significant yields and be cost-effective.